PENUNJUKAN PENASEHAT HUKUM TERHADAP ANAK DI BAWAH UMUR OLEH PENYIDIK DALAM PROSES PENYIDIKAN DI KEPOLISIAN SEKTOR SAMARINDA KOTA - Eka Ramadhani Anantha (Universitas 17 Agustus 1945 Samarinda, 2019)
AbstractIndonesia is a nation of laws and manages underage’s law as well. It written on Republic Indonesia Act No 11, 2012 about Underage Judicature System, it talks about the principles of protection, justice, non-discrimination, prime need, recognition of children opinion, life continuance, child growth, child mentoring, proposionality, deprivation of independency, being convicted as the last efort, and reprisal avoidance .This research showed in Samarinda City Police Department, legal counsel appointee by investigator toward underage investigation process in Samarinda Police Department is underage children (juvenile) who are dealing with legal issues have rights to receive legal assistance as to be accompanied by legal counsel according to Child Protection Act No 23 Section 17 article 2, 2002.This research also got the legal assistance pattern of underage who is dealing with legal issues in criminal laws. The underage is going to get investigation by the investigator. On dealing with juvenile deliquency, The police who has the duty as the juvenile investigator in Women and Child Protection Unit in Samarinda Police Department will receive a decree by the Samarinda Police Chief. The juvenile investigator must have interest, concern, dedication, and know the most problem a children might face by give them mentoring, child growth knowledge, ordinances and society value knowledge. Keywords: Underage, Investigator, Investigation